Obtenção de carvão ativado modificado químicamente a partir de resíduos de podas de árvores e aplicação na remoção de fármacos em meio aquoso - Davies, Fernando Souza (2025)
The production of chemically activated carbon (CA) from the use of tree pruning waste is a way to make good use of this waste, due to environmental and economic concerns. This study proposed the use of tree pruning waste from the mango (Mangífera indica) and Indian earring (Cojoba arbórea) species for the production of chemically activated carbon using zinc chloride (ZnCl2) as an activator. The already crushed waste was obtained from the city hall of São Miguel do Iguaçu-PR and was subsequently air-dried at room temperature for 30 days. Following drying, charcoal was produced in a muffle furnace by carbonizing the waste at a temperature of 700 °C for 2 hours. The activation was also performed in a muffle furnace using a 2² Complete Factorial Design with central points, and a Central Composite Rotational Design (CCRD) to optimize the conditions in terms of temperature and ratio between the amount of activator and charcoal using as a response the amount of acid groups (mEq g-1) present in the charcoals obtained. The ideal conditions for the production of activated carbons were defined through data regression analysis and response surface methodology, obtaining the ideal conditions for the mango (MG-T1) of 331 ºC and ZnCl2/charcoal ratio of 2.4, while the optimal conditions for Indian earring (BI-T2) of 239 ºC and ZnCl2/charcoal ratio of 2.68. After this definition, a larger quantity of activated carbon was produced for characterization for use in drug adsorption. At this stage, the zero charge potential (pHpcz) of the charcoals was determined and the target drug of the research was defined, with sulfachlorpyridazine (SCP) being chosen because it presented the highest percentage of removal among the 6 drugs tested (tetracycline, chloramphenicol, sulfachlorpyridazine, sulfamethoxazole, metformin and ciprofloxacin). With the definition of the drug, the kinetic study and adsorption isotherms were performed, using temperatures of 25, 30 and 35 °C and analysis times of 0 to 420 minutes. The kinetic study indicated the pseudo-second-order model as the most appropriate to fit the experimental data of the adsorption of SCP by activated carbon from Cojoba arbórea for treatment 2 (BI-T2), while the Elovich model best fitted the data of activated carbon from Mangífera indica for treatment 1 (MG-T1). The adsorption isotherms indicated that the Langmuir model adequately describes the process for both carbons, suggesting monolayer adsorption.